Implementation of Project-Based Learning in Improving Critical Thinking Skills of Middle School Students - Ahmad Nur Kholis (Archipel: Journal of Indonesian Interdisciplinary Studies, 2026)
This study aims to examine the implementation of project-based learning in improving the critical thinking skills of high school students through a qualitative approach. The background of the study stems from the demands of 21st-century education that emphasize higher-order thinking skills, while conventional learning practices still tend to be memorization-oriented and teacher-centered. The project-based learning approach is considered relevant because it provides authentic learning experiences that require active student involvement in problem-solving. This study used a case study design with teachers and students directly involved in project-based learning. Data collection was conducted through classroom observations, in-depth interviews, and analysis of learning documents. Data analysis was conducted thematically through the stages of reduction, presentation, and drawing conclusions. The results show that project-based learning encourages a change in the role of teachers to facilitators and increases student participation, independence, and reflective abilities. Project activities train students in analyzing problems, evaluating information, and making decisions based on arguments. The collaborative learning environment and evaluation that emphasizes the thinking process strengthen the development of critical thinking skills. This study concludes that project-based learning is an effective and relevant pedagogical strategy for developing high school students' critical thinking skills in a sustainable manner.